ClpA affects the virulence of Paracidovorax citrulli on melon by regulating RepA - Ziye, Shang; Yuqiang, Zhao; Shitong, Wu; Ling, Cai; Chenchao, Sun; Jun, Wang; Weirong, Gong; Yanli, Tian; Baishi, Hu (Frontiers in Microbiology, 2024)
ClpA is a widely conserved protease in bacteria that plays a key role in virulence. To investigate its specific mechanism of action in the pathogenicity of Paracidovorax citrulli (formerly Acidovorax citrulli), we constructed a ClpA deletion mutant, ΔClpA. The ΔClpA mutant of P. citrulli displayed reduced virulence on melon seedlings, and reduced motility, swarming ability, and antioxidant capacity. On the other hand, the ClpA deletion of P. citrulli mutant reduced the resistance to elevated temperature and enhanced biofilm formation ability. Using qRT-PCR, we observed that ClpA negatively regulates the expression of the virulence-related genes virB, pilR, pilA, and fliM, while positively regulating hrpG, hrcQ, and trbC. Bacterial double hybrid and Glutathione-S-transferase pulldown (GST-pulldown) results showed that ClpA interacts directly with RepA, and negatively regulates the expression of RepA. After deletion of the RepA gene, the pathogenicity of P. citrulli was lost, biofilm formation ability was enhanced, and the expression of hrpG, pilR, and trbC was positively regulated. These results indicate that ClpA plays a key role in the regulation of several virulence traits of P. citrulli, paving the way for future studies to better elucidate the virulence mechanisms of this bacterial plant pathogen.